How Lobbying Affects Representation: Results for Majority-Elected Politicians - David Stadelmann; Marco Portmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2015)
Combining referendum results with parliamentary votes of proportionally-elected politicians of the Swiss Lower House of Parliament, Giger and Klüver (American Journal of Political Science, forthcoming) find that sectional and cause interest groups affect the quality of political representation. We extend their analysis to a new dataset of majority-elected politicians of the Upper House. Our results show that sectional and cause groups do not affect defection of politicians from their constituents. This suggests that the electoral system moderates the influence of interest groups on political representation.
Keywords: 330; Interest groups; representation; referenda; MP defection; electoral systems